The effect of CRP/albumin ratio on prognosis of hospitalized patients due to COVID-19 - Ayşe Alga Batırel; Sevtap Acer; Nilüfer Zorlutuna Kaymak; Gizem Dogan Gokce; Mehmet Tezcan; Nesrin Şen (SERNEV, 2022)
Introduction: COVID-19 disease caused by the SARS-Cov-2 virus is characterized by clinical spectra of varying severity. Coagulopathy and inflammation are the most important factors associated with COVID-19 severity. The use of a biomarker of inflammation and coagulation factors has not yet been clarified. The present study aimed to examine the role of CRP/Albumin, an inflammation marker, in predicting the course of COVID-19 disease.Methods: The Demographic, laboratory, and prognosis of 457 patients who were hospitalized during the COVID-19 pandemic service between April and May 2020 were analyzed retrospectively. The relationship between the patients' CRP/Albumin ratio and disease severity, length of hospital stays, and prognosis were analyzed.Results: The rate of hospitalization in the intensive care unit was 10.5% (n=48), mechanical ventilation was 8.1% (n=37), and death was 1.3% (n=6). The CRP/albumin ratio was statistically higher in those with lung infiltration (p=0.005), those who were taken to the intensive care unit (p lt;0.001), and those who needed mechanical ventilation (p lt;0.001). A positive significant correlation was found between the length of hospital stay and the CRP/albumin ratio(r=0.412, p lt; 0.001).Conclusion: The CRP/Albumin ratio is thought to be an auxiliary marker for doctors in the early transfer of patients to the intensive care unit, the early detection of those in need of MV, and the determination of lung infiltration.Keywords: COVID-19, CRP/albumin ratio, prognosis